H6-type transformerless single-phase inverter for grid-tied photovoltaic system - Islam, M.; Mekhilef, Saad (Institution of Engineering and Technology (IET), 2015)
There has been an increasing interest in transformerless inverter for grid-tied photovoltaic (PV) system because of the benefits of lower cost, smaller volume as well as higher efficiency compared with the ones with transformer. However, one of the technical challenges of the transformerless inverter is the safety issue of leakage current which needs to be addressed carefully. In addition, according to the international regulations, transformerless inverter should be capable of handling a certain amount of reactive power. In this study, a new H6-type transformerless inverter for grid-tied PV system is proposed that can eliminate the threat of leakage current. The proposed topology has also the capability to inject reactive power into the utility grid. Three-level output voltage employing unipolar sinusoidal pulse-width modulation can be achieved with the proposed topology. The proposed topology structure and detail operation principle with reactive power control are investigated. The relationship among the existing topologies and their reactive power control capability are also discussed. The proposed topology is simulated in MATLAB/Simulink software to initially verify the accuracy of theoretical explanations. Finally, a universal prototype rated 1 kW has been built and tested. The experimental results validate the theoretical analysis and simulation results.